In Vivo Response of Growth Plate to Biodegradable Mg-Ca-Zn Alloys Depending on the Surface Modification - Song, Mi Hyun (Int J Mol Sci, 2019)
Because Mg-Ca-Zn alloys are biodegradable and obviate secondary implant removal, they are especially beneficial for pediatric patients. We examined the degradation performance of Mg-Ca-Zn alloys depending on the surface modification and investigated the in vivo effects on the growth plate in a skeletally immature rabbit model. Either plasma electrolyte oxidation (PEO)-coated (n = 18) or non-coated (n = 18) Mg-Ca-Zn alloy was inserted at the distal femoral physis. We measured the degradation performance and femoral segment lengths using micro-CT. In addition, we analyzed the histomorphometric and histopathologic characteristics of the growth plate. Although there were no acute, chronic inflammatory reactions in either group, they differed significantly in the tissue reactions to their degradation performance and physeal responses. Compared to non-coated alloys, PEO-coated alloys degraded significantly slowly with diminished hydrogen gas formation. Depending on the degradation rate, large bone bridge formation and premature physeal arrest occurred primarily in the non-coated group, whereas only a small-sized bone bridge formed in the PEO-coated group. This difference ultimately led to significant shortening of the femoral segment in the non-coated group. This study suggests that optimal degradation could be achieved with PEO-coated Mg-Ca-Zn alloys, making them promising and safe biodegradable materials with no growth plate damage.